TAX PLANNING AND THE TIMELINESS OF FINANCIAL REPORTING IN LISTED MANUFACTURING FIRMS IN NIGERIA - Ikponmwosa Michael Igbinovia; Amaka Nkiru Unamma (Malete Journal of Accounting and Finance)
The timeliness of financial reports is a critical aspect of management and reporting, and its connection with tax planning in Nigeria's manufacturing sector seems complex and multifaceted. This study investigates the impact of tax avoidance and tax planning strategies on the timeliness of financial reporting using a sample of 28 manufacturing firms in the Nigeria exchange group for the period 2015 to 2022. The result of the binary logistic (logit) regression analysis consisting of 224 firm-year observations revealed that at 5 % significance level, tax avoidance as measured by book tax difference and effective tax rate does not significantly influence the timeliness or otherwise of financial reporting in Nigeria manufacturing firms. Similarly, capital intensity, a measure of tax planning strategy exerts an insignificant negative effect on the timeliness or otherwise of financial reporting in Nigeria manufacturing firms. However, the study observed that leverage, a measure of tax planning strategy, is a significant determinant of the timeliness of financial reporting in Nigeria manufacturing firms. The study concludes that the delay on timely financial reporting orchestrated by tax planning is not significant enough to cause delays outside the statutory 90-day period. The study recommends that Managers take full advantage of tax avoidance and tax planning within the context of relevant tax laws, as they do not dampen firms’ ability to produce timely financial reports.